Effectiveness of Blood Glucose Time in Range to Reduce Risk of Blood Glucose Extrusion and Improve Blood Glucose Metrics in Type 1 Diabetic Patients - Oraibi, Omar; Somaili, Mohammed; Elmakki, Erwa; Alqassimi, Sameer; Madkhali, Mohammed A.; Mohrag, Mostafa; Abusageah, Faisal; Alhazmi, Mohammed; Alfaifi, Samar; Ageeli, Ruba; Sumayli, Mohammed; Arishi, Fatimah; et al. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background: With evolving diabetes technology, continuous glucose monitoring (CGM) and time in range have been advanced as critical measurements to assess complications. They have shown improvement in A1C levels and decreased episodes of blood glucose extrusion. Aims: This study aimed to assess the awareness and utilization of blood glucose time in range and its effectiveness in reducing the risk of blood glucose extrusion and improving blood glucose metrics among patients with type 1 diabetes mellitus. Methods: A retrospective study included 342 patients who met the inclusion criteria and were using the CGM, aiming for a TIR of 70% daily. Glycemic control was followed using TIR data, blood glucose extrusion frequency (including hyperglycemia and hypoglycemia events), active sensor time, average blood glucose, and glucose management indicator (GMI) levels. Results: A total of 342 individuals participated in this study, the majority of whom were below 18 years of age (62.3%). The hypoglycemic frequency was significantly increased compared to the baseline, and most participants experienced hypoglycemia events (p = 0.0001). The incidences increased over time, with 90.9% and 93% having hypoglycemia at 60 and 90 days (p = 0.0001), respectively. The active scan and sensor time were not followed, which led to the blood glucose target not being achieved, with no improvement throughout the study. Consequently, no improvement occurred in glycemic control. Conclusion: CGM technology has been promising and proven effective in improving glycemic. However, our study did not show these benefits as expected, which could be explained by the underutilization and improper use of the CGM.
Keywords: hyperglycemia